(untitled) (Dhaka University Journal of Biological Sciences, 2023)
With the increased aggressive behavior observed among the children and adolescents in Bangladesh, it is pressing to investigate plausible aggression scripts acquired in childhood that may cause aggressive behavior at a later age. Normative Beliefs about Aggression Scale (NOBAGS) is such a popular tool to identify aggression scripts by measuring children’s cognitive dispositions toward aggressive behavior. The current study culturally adapted and psychometrically validated the NOBAGS for elementary school students. After translating all 20 items, it was administered to 210 children (pilot: 30, field study: 180), ages ranging from 10 to 11 years, recruited from two different schools in Dhaka using the convenience sampling method. The Bangla NOBAGS retained all 20 items of the original scale with a latent structure of six correlated components. The Bangla NOBAGS showed satisfactory reliability estimates (Total scale: McDonald’s ωt =.96; subscales McDonald’s ωt: .68-.90) and validity evidence. The psychometric sound properties of the Bangla NOBAGS suggest the plausible use of this scale to assess elementary school children’s perception towards aggressive behavior. Dhaka Univ. J. Biol. Sci. 31(2): 243-255, 2022 (July)